(untitled) - Picker, Anne Dolganos (Hoboken, N.J., 2007)
International Economic Indicators and Central Banks opens with a brief description of the bond, stock, and foreign exchange markets—since this is where investors respond to the news of central bank activities and the direction of economic indicators. Following this market introduction, Part I moves on to provide you with an eye-opening overview of central bank functions, and then hones in on the individual central banks of the countries previously mentioned. Here, you'll discover how these central banks operate, and why they influence economies and your investments. Part II of the book deals with the nitty-gritty of market-moving international economic indicators—from where to find them and what they mean to when they're released. With each chapter devoted to a different country, you'll become familiar with indicators that are reliable gauges of a country's economic growth and discover how similar indicators may differ across geographical borders. Some of the indicators addressed include the United Kingdom's Gross Domestic Product statistics, Canada's Labour Force Survey (LFS), and Japan's Tankan Survey.
Keywords: Economic forecasting,Economic indicators,Investments; Decision making